In vivo biocompatibility study of zirconium dioxide nanoparticles for its applicatioin in Dental treatment - VANI C; JAYA DEEPIKA S; KALIDASS SUBRAMANIAM (International Journal of Pharma and Bio Sciences, 2017)
Zirconia is also known as zirconium dioxide (ZrO2), an inorganic polycrystalline material and is widely used in the field of dental treatment. Due to its mechanical and optical properties, Zirconia has been used in dentistry with a 90% content made up of Zirconia as dental crowns. This Zirconia based ceramics in dental prosthetics leads to cause toxic reactions and delayed allergic responses in oral tissues which may also lead to cause oral cancer. The main aim of our study is to synthesis Zirconia nanoparticles, which has increased surface area and may be less toxic than Zirconia particles in dental treatment. In our present study the synthesis and characterization of Zirconia nanoparticles was performed and the size obtained was 50-70 nm. Biocompatibility study of Zirconia nanoparticles were performed using chick embryo as In vivo model system. Different concentrations of Zirconia nanoparticles were tested for the antioxidant enzyme studies in chick embryos. The liver and heart tissues of the embryos were examined for estimation of Glutothione peroxidase, Lipid peroxidase and Superoxide dismutase in the zirconia nanopartilces treated groups (10 PPM, 20 PPM, 40 PPM and 80 PPM). The increased amount of total proteins(35 mg/ml), superoxide dismutase(6.91 Units/mg Protein) and glutathione peroxidase (6.395 Units/mg Protein) and decreased amount of lipid peroxidation ( 4.99 n mol/mg Protein) was recorded in 80 PPM nanoprticles treated group when compared to that of the control and heart tissue samples of other treatments also.